Ballistic performance of Kevlar fabric impregnated with nanosilica/PEG shear thickening fluid. (1st April 2019) - Khodadadi, A.; Liaghat, Gh; Vahid, S.; Sabet, A.R.; Hadavinia, H.
Abstract: This study presents the response of fiber reinforced composite material composed of woven Kevlar fabric impregnated with a colloidal shear thickening fluid (STF) under high velocity impact loading. The STF was made by dispersing silica nanoparticles at 15, 25, 35 and 45 wt.% loading in polyethylene glycol. The effects of silica nanoparticle loading on energy absorption and ballistic limit were studied experimentally. Rheological results revealed that shear thickening occurred at all four nanosilica loading and higher loading showing the higher shear thickening at lower shear rate. SEM images confirmed good dispersion of nanosilica particles in the suspension. The results of the pull out test show that by increasing nanosilica loading, the force required to pull the yarn out from the fabric impregnated by STF increases. Impact resistance performance of Kevlar fabric is significantly enhanced due to the presence of STF. Although high velocity impact results show that by increasing nanosilica loading, the energy absorption of composites increases, but in high loading of nanosilica, the effectiveness of STF decreases. For further investigation, the energy absorption at the ballistic limit was normalized by the areal density of the neat and impregnated fabrics to give the specific energy absorption (SEA). It is found that the SEA of 15 wt.% nanosilica loading is lower compared to the neat fabric. Also the highest SEA turn out in the case of 35 wt.% STF/Kevlar composites in which the SEA is 2.3 times larger than those of the neat fabric.